Direct application of cobaltite-based perovskite cathodes on the yttria-stabilized zirconia electrolyte for intermediate temperature solid oxide fuel cells. Issue 45 (7th November 2016) - Chen, Kongfa; Li, Na; Ai, Na; Li, Meng; Cheng, Yi; Rickard, William D. A.; Li, Jian; Jiang, San Ping
Abstract : Cobaltite based perovskites can be directly applied on the YSZ electrolyte via an in situ polarization induced electrode/electrolyte interface. Abstract : In this communication, cobaltite-based perovskite (CBP) cathodes are directly applied on the yttria-stabilized zirconia (YSZ) electrolyte via an in situ assembly process without the addition of a doped ceria interlayer and pre-sintering at high temperatures. The results demonstrate for the first time that a CBP electrode/YSZ electrolyte interface can be formed in situ under cathodic polarization at a solid oxide fuel cell (SOFC) operating temperature of 750 °C. Nevertheless, the performance of cells with Sr-containing CBP cathodes deteriorates due to the surface segregation of Sr species and formation of a Sr-rich reaction layer at the interface. However, the stability and power density of cells with in situ assembled CBP cathodes can be further enhanced by B-site doping or by using a Sr-free CBP. The direct application of CBPs on the YSZ electrolyte revolutionizes the design of intermediate temperature SOFCs.